Plasma Medicine - Concepts and Clinical Applications 2018
DOI: 10.5772/intechopen.76094
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange in Clinical Practice

Abstract: Plasma exchange (PEX) is a treatment method with increasing range of indications. However, due to the small number of randomized trials, its effectiveness is still under debate in certain conditions. The aim of our chapter is to present the major principles of PEX, discuss safety issues and reveal current data for treatment effectiveness of the method. Novel indications for PEX will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This translates to greater removal of immune complexes but with debatable effects on immunomodulation in sepsis. 6,45 Head-to-head trials comparing membrane and centrifugal TPE procedures in patients with severe sepsis have not been performed; studies involving patients without sepsis but required TPE reported equivocal results between these 2 modes. 46,47 Our review suggests no significant difference in outcome between centrifugal and membrane TPE.…”
Section: Discussionmentioning
confidence: 99%
“…This translates to greater removal of immune complexes but with debatable effects on immunomodulation in sepsis. 6,45 Head-to-head trials comparing membrane and centrifugal TPE procedures in patients with severe sepsis have not been performed; studies involving patients without sepsis but required TPE reported equivocal results between these 2 modes. 46,47 Our review suggests no significant difference in outcome between centrifugal and membrane TPE.…”
Section: Discussionmentioning
confidence: 99%